The Correlation Between Leg Power Endurance and Arm Power Endurance with Breaststroke Swimming Performance - Muhammad Ramdhani Raja Saputra; Agus Rusdiana; Unun Umaran (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aimed to determine the relationship between leg power endurance and arm power endurance and the performance of the 50-meter breaststroke among athletes of the Tendy Swimming Club. The study employed a quantitative method with a correlational approach. The population and sample consisted of 15 athletes selected using a total sampling technique. The research instruments included the hurdle jump endurance test to measure leg power endurance, the clapping push-up test to measure arm power endurance, and a 50-meter breaststroke swimming test to measure swimming performance. Data analysis was conducted using descriptive statistics, the Shapiro–Wilk normality test, and the Pearson correlation test at a significance level of α = 0.05. The results showed a strong and significant negative relationship between arm power endurance and 50-meter breaststroke performance (r = −0.656; p < 0.05), as well as a very strong and significant negative relationship between leg power endurance and 50-meter breaststroke performance (r = −0.922; p < 0.05). These findings indicate that higher levels of leg and arm power endurance are associated with faster swimming times. Therefore, it can be concluded that leg and arm power endurance have a significant relationship with 50-meter breaststroke performance, with leg power endurance showing a more dominant contribution and requiring special attention in swimming training programs.